DOES THE NUMBER OF BORROWERS PER LOAN OFFICER INFLUENCE MICROFINANCE INSTITUTION ASSET QUALITY? A STOCHASTIC FRONTIER ANALYSIS - Pal, Debdatta; Mitra, Subrata K. (Investigación Económica, 2017)
Employing stochastic frontier analysis, this paper explores whether there is trade-off between the number of borrowers per loan officer and microfinance institution (MFI) asset quality, represented by the portfolio value at risk. It uses a dataset with information from 1,575 MFIs from 109 countries for the period 2006-2013. We find corroborative evidence that there is no trade-off between the number of borrowers per loan officer and MFI asset quality, which contravenes the conventional wisdom. We show that MFIs have reaped the benefit of economies of scale without compromising asset quality. These findings remain significant across ownership types and regardless of deposit-taking status.